Collaborative Governance and Hoax Politics in The Era of Covid-19 in Makassar City - Rudi Hardi; Hardianto Hawing (Mengeja Indonesia Publisher, 2022)
The spread of political hoaxes is quite massive and fast. As the coming political year approaches, inter-community friction may occur due to the spread of hoax news and can cause anxiety, hatred, and hostility in society. As a result, if it continues and is not controlled, it will result in conflicts between individuals and different groups. This study aims to find a Collaborative Governance model to prevent the spread of political hoaxes. This study uses a qualitative approach to reveal the forms and types of hoaxes on social media and reveal hidden values. The data collection method used focused observation techniques, in-depth interviews, and documentation. The results of the study show, namely: Frist, a political hoax is a form of Cyber Crime that seems simple easy to do but has a significant impact on people's social life. Second, types of political hoaxes, including, namely Satire or Parody, Misleading Content, Counterfeit Content, Fake Content, Wrong Connections, False content, and manipulated content. The strategy for dealing with political hoaxes is the movement to educate the public to be more critical in politics. The government must be supported by elements of education, independent state institutions, and other social institutions. The political literacy movement is a comprehensive effort that involves all parties and elements intensely and continuously in the fight against lies. Apart from values and norms, legal, social, and religious instruments must be included there. Political hoax must be considered a social disaster in the political space.